(untitled) (Journal of Comparative & International Higher Education, 2022)
Higher Education in the Era of Migration, Displacement and Internationalization by Khalid Arar, Yasar Kondakci, Bernhard Streitwieser, and Anna Saiti provides a multifaceted exploration of the dilemmas involved in higher education policymaking and administration in keeping with the accelerated pace, scale, and diversity of transnational migration. Assuming that higher education empowers displaced persons to better themselves and their host communities, Arar et al. consider specific dynamics that shape the educational trajectories and choices available to these populations. The co-authors list activities and initiatives employed in various world states to create higher education pathways for displaced persons, highlighting different variables that affect policies and indicating the hurdles faced by the populations being served and the institutions supporting them. These country-specific examinations of approaches facilitating access are the richest contributions of the book. The discussion of the gendered dimensions of migration is less rewarding. Ultimately, this book is a timely investigation and can inform and improve higher education policies, practices, and narratives concerning displaced and refugee students.